Affective false memories in Dementia of Alzheimer's Type. (March 2017) - Fairfield, Beth; Colangelo, Mirco; Mammarella, Nicola; Di Domenico, Alberto; Cornoldi, Cesare
Abstract: This study examined the production of inferential false memories for complex pictorial stimuli and the implications of affective content in Alzheimer's disease (AD). A group of 24 AD patients and a group of 24 healthy older adults studied a sequence of pictures depicting stories that included positive, negative or neutral consequences of an unseen action, and then completed an old-new picture recognition test. The number of causal errors was higher in healthy older adults compared to AD patients but affective content attenuated the effect. Causal errors increased in AD patients when stories included affective (positive or negative) outcomes. In addition, negative content produced a larger number of errors than positive content across groups. This data confirms that although memory processing is poorer in AD, it is sensitive to affective content. Accordingly, the nature of affective false memory errors suggest the need to consider the use of affective information in the development of new cognitive training procedures. Highlights: Memory processing in AD is sensitive to affective content. False memories increase with negative content. False memories may be used to discriminate between healthy and pathological aging.